THE PHRASES IN KARO LANGUAGE - Ginting, Herlina; Ginting, Adelina (Pendidikan Bahasa Indonesia dan Sastra (PENDISTRA), 2021)
This study describes the various types and the function of phrase in Karo language. Based on the form, phrase can be distinguished into coordinative phrase, modifier phrase, and exocentric phrase. Based on the function, phrase can be distinguished into (1) noun phrase which function as a subject or an object, (2) verb phrase as a predicate, (3) adjective phrase as a noun modifier, (4) adverb phrase or prepositional phrase as a verb modifier